(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The paper presents India’s foreign policy aspirations for socio-economic development, security and peace which depends on a peaceful and prosperous neighbourhood with Afghanistan, is a road for such design. The geo-strategic location of Afghanistan provides a suitable route for India to achieve her objectives in the regional and global context. When the war on Afghanistan in response to the September 11, 2001 attacks on the United States displaced the Taliban in 2001, India moved quickly to assist in reconstruction of Afghanistan and providing financial aid. India’s assistance and support to Afghanistan cover a wide range of issues to include trade, commerce and security and to ensure a stable and democratic Afghanistan. Moreover, India seeks to project itself as a dominant regional power and sees the building of stable, long-term relations with Central Asian Republics (CARs) and to counter Pakistani and Chinese influence in the region.